Determination of pKa Values for Acrylic, Methacrylic and Itaconic Acids by 1H and 13C NMR in Deuterated Water - Ibarra-Montaño, Emma Lilia; Rodríguez-Laguna, Norma; Sánchez-Hernández, Aníbal; Rojas-Hernández, Alberto (Journal of Applied Solution Chemistry and Modeling, 2015)
Acrylic, methacrylic and itaconic acids have Brønsted acidity given by carboxylic groups, and they are extensively used in polymerization for modification of several soft-mater materials. By this reason it is important to propose better characterization studies and alternatives to obtain more of their physicochemical properties. In this work the pKa values of these acids are obtained by adjusting NMR chemical shifts for hydrogen and carbon nuclei as a function of pH with program HYPNMR, and compared with those obtained by potentiometric and conductometric titrations.